2012
DOI: 10.1021/ic202096x
|View full text |Cite
|
Sign up to set email alerts
|

Spectroscopic Characterization of Active-Site Variants of the PduO-type ATP:Corrinoid Adenosyltransferase from Lactobacillus reuteri: Insights into the Mechanism of Four-Coordinate Co(II)corrinoid Formation

Abstract: The PduO-type ATP:corrinoid adenosyltransferase from Lactobacillus reuteri (LrPduO) catalyzes the transfer of the adenosyl-group of ATP to Co1+cobalamin (Cbl) and Co1+cobinamide (Cbi) substrates to synthesize adenosylcobalamin (AdoCbl) and adenosylcobinamide (AdoCbi+), respectively. Previous studies revealed that to overcome the thermodynamically challenging Co2+→Co1+ reduction, the enzyme drastically weakens the axial ligand–Co2+ bond so as to generate effectively four-coordinate (4c) Co2+corrinoid species. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
49
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
2
1

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(49 citation statements)
references
References 48 publications
0
49
0
Order By: Relevance
“…In support of this proposal, we have recently shown that alanine substitutions of active site residues located in the plane of the corrin ring drastically lower the relative yield of four-coordinate Co(II)rrinoid formation achieved by the Lr PduO/ATP complex. 38 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In support of this proposal, we have recently shown that alanine substitutions of active site residues located in the plane of the corrin ring drastically lower the relative yield of four-coordinate Co(II)rrinoid formation achieved by the Lr PduO/ATP complex. 38 …”
Section: Discussionmentioning
confidence: 99%
“…Yet, it is obvious that non-bonding (electrostatic/hydrophobic) interactions between the corrin ring and the enzyme active site must play an important role in the mechanism of axial ligand removal, as amino acid substitutions in Lr PduO that disrupt the interactions between the peripheral amide groups of the corrin ring and the enzyme active site result in a significantly decreased yield for the five- to four-coordinate Co(II)rrinoid conversion and thus slow down the formation of AdoCbl. 37,38 …”
Section: Introductionmentioning
confidence: 99%
“…Eº(NHE) = −228 mV for FMN at pH 7.5) 26,27 or by reduced flavoproteins in the case of Se CobA (Eº(NHE) = −440 mV for the semiquinone/reduced flavin couple of FldA, the purported physiological partner of Se CobA). 2830 Extensive biochemical, 31,32 crystallographic, 3235 and spectroscopic studies 3638 of Se CobA and different PduO-type ACATs have revealed that a structurally unique four-coordinate (4c) Co(II)Cbl species is generated by these enzymes in the presence of ATP. The most recent X-ray crystal structures reported for Se CobA and Lr PduO complexed with Co(II)Cbl and MgATP have provided evidence that the DMB moiety that occupies the Coα position of Co(II)Cbl in solution is displaced by a non-coordinating phenylalanine residue (F112 in Lr PduO and F91 in Se CobA).…”
Section: Introductionmentioning
confidence: 99%
“…In support of this proposal, it has been shown that amino acid substitutions in the active sites of the CobA- and PduO-type ACATs aimed at altering the relative positioning of the two substrates could cause a significant decrease in catalytic activity, despite the fact that the variants retained the ability to generate sizable amounts of 4c Co(II)Cbl. 16,17 …”
Section: Discussionmentioning
confidence: 99%
“…11,15 Spectroscopic characterization of enzyme variants revealed that the driving force for the displacement of the DMB ligand is provided by the formation of favorable interactions among active site residues when 4c Co(II)Cbl is generated. 16,17 …”
mentioning
confidence: 99%